Breslauer Germanistikstudenten schreiben Magisterarbeiten: Rückblick, Jetzt-Zustand und Ausblick - Lesław Cirko (Beiträge zur Allgemeinen und Vergleichenden Sprachwissenschaft)
The way master theses are prepared in the Department of German Studies, University of Wrocław has changed over the last thirty years. The main objective of the present paper is to show how students’ motivation has changed. The Bologna Process seems to be an important time frame, and at the same time a reason for many negative developments observed by the author. The paper addresses also what the author considers insufficient preparation of students to participate in the academic discourse, and the lack of knowledge about the true causes of students’ problems among lectures and professors. The author suggests that the seminar “Academic Writing”, introduced recently in the Department of German Studies may be a solution to the aforementioned problems.